(3JWhQ GdJGQjN GdGbJUGOj GdESdGej hGdhVYj (B/s - (3eUWai, CMeO aQjOs ((3GdGScfOQjI(B: s (3eDSSI THGH GdLGeYI(B, s, 2007)
(3jVe eQMdI Jchjf GbJUGOjGJ GdYGde, eUGOQ GdJehjd aj GdYUQ GdGSdGej, YUQ GdNdaGA GdQGTOjf, eQMdI GdfVL aj GbJUGOjGJ GdYGde GdGSdGej, eQMdI GdQchO hGdJNda aj GbJUGOjGJ GdYGde GdGSdGej, GdfXGe GdGbJUGOj j GQhHG, ePgH GdJLGQjjf hXghQ GdQCSeGdjI GdJLGQjI, GdQCSeGdjI GdUfGYjI, GdJWhQGJ GdGbJUGOjI aj GQhHG HYO GdKhQI GdUfGYjI, GdeTGcd GdGbJJUGOjI ajeG Hjf GdMQHjf GdYGdejJjf, GdJWhQ GdJGQjNj ddGJaGbjI GdYGeI ddJYQjaGJ hGdJLGQI, Cge GdfJGFL GdJj JeNVJ YfgG LhdI ChQhLhGj, GdCKGQ GdeQJbHI dLhdI GhQhLhGj Ydi GdOhd GdYQHjIs
(3HHdjhZQGajG(B: (3U(B.218-219s
Keywords: (3GdGbJUGO GSdGejs; (3GdGbJUGO(B-(3JGQjNs; (3GdJGQjN GdGbJUGOjs